RANCANG BANGUN SISTEM INFORMASI PELAYANAN MASYARAKAT BERBASIS WEB PADA KANTOR KECAMATAN MESUJI MENGGUNAKAN METODE RATIONAL UNIFIED PROCESS (RUP) - Alfan Ardi Putra; Dani Anggoro; Mustika (Universitas Muhammadiyah Metro, 2025)
The problem that occurs in the public service system at Mesuji Timur District is that the process of submitting letters is still carried out manually, resulting in service delays, inefficiency, and a high risk of errors in recording and validating documents. People have to come directly to the district office with physical requirements, which consumes time, effort, and costs. To overcome these issues, this research applies the Rational Unified Process (RUP) method, which consists of the inception, elaboration, construction, and transition phases. The objective of this study is to design and develop a web-based public service information system that facilitates the process of submitting, validating, and printing letters digitally. The results show that the developed system can accelerate the service process, minimize administrative errors, and enable citizens to apply for letters online anytime and anywhere. The conclusion of this research is that the implementation of the RUP method successfully produces an effective and efficient web-based public service information system that supports the improvement of service quality at Mesuji Timur District.